Fracture analysis of chiral fiber-reinforced biocomposite. (August 2022) - Dong, J.J.; Xu, L.; Yu, H.J.; Wang, J.S.; Qin, Q.H.
Highlights: A fracture mechanics model of chiral fiber biocomposite is developed. The analytical solutions of the stress and couple stress near the crack tip are obtained. The results show that the chiral microstructures can strengthen the fracture toughness. Abstract: The widely presented chiral microstructures in biological materials such as wood, bone and climbing tendrils, bring up biological materials with favorable elasticity, fracture toughness and impact resistance. A tricky thing is, how the chiral microstructures could affect the fracture behaviors of this category of materials is not clear. In this paper, a fracture mechanics model of chiral fiber composite under mode I loading is established for investigating the effects of chiral microstructures on the fracture behaviors of corresponding materials. The analytical solutions of the stress and displacement fields near the crack tip are obtained by using the potential function method. The finite element method (FEM) for chiral materials is implemented into ABAQUS and corresponding simulation is conducted. The theoretical results are consistent with those from simulations. The effects of chiral coefficients on the stress concentration and the stress intensity factor are investigated. The results show that the couple stresses induced by the chiral microstructure can significantly decrease the stress concentration near the crack tip. Furthermore, the chiral microstructures can hinder the crack propagation and thus strengthen, to a certain extent, the fracture toughness of the biological materials. It is expected this work can enhance our understanding on the relationship between microstructure and properties of biological materials, and contribute to the biomimetic design and preparation of high-performance materials.